Direct synthesis of H2O2 from H-2 and O-2 over Pd/H-beta catalyst in an aqueous acidic medium: influence of halide ions present in the catalyst or reaction medium on H2O2 formation - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
The influence of different halide ions present in the catalyst or reaction medium on the performance of Pd/H-beta catalyst in the direct H2O2 synthesis in an aqueous acidic (0.03 M H3PO4) reaction medium at 27 degrees C and atmospheric pressure has been thoroughly investigated. The results showed a strong influence of both the bulk Pd oxidation state in the catalyst and the halide ions added to the reaction medium on the performance of the catalyst in the H-2 to H2O2 oxidation, H2O2 decomposition/hydrogenation reactions. The different ammonium halides impregnated reduced Pd/H-beta catalyst calcined in inert (N-2) and oxidizing (air) gaseous atmospheres also revealed that the bulk Pd oxidation state and nature of the halide ions present in the catalyst together control the overall performance of the catalyst in the H2O2 formation reaction. The presence of halide ions in reaction medium or in the catalyst significantly changes the selectivity for H2O2 formation in the direct H2O2 synthesis. Bromide ions are found to remarkably enhance the H2O2 selectivity in the direct H2O2 synthesis irrespective of the Pd oxidation state in the catalyst. The promoting action of Br- is attributed mainly to the large decrease in the H2O2 decomposition and hydrogenation activities of the catalyst and also inhibition for the non-selective H-2-to-water oxidation over the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H-P supported Pd catalyst; H2O2 decomposition; H2O2 hydrogenation; promoting action of bromide ions